Suppressive Effect of Insulin on the Gene Expression and Plasma Concentrations of Mediators of Asthmatic Inflammation - Husam Ghanim; Kelly Green; Sanaa Abuaysheh; Manav Batra; Nitesh D. Kuhadiya; Reema Patel; Antoine Makdissi; Sandeep Dhindsa; Ajay Chaudhuri; Paresh Dandona (Journal of Diabetes Research)
Background and Hypothesis. Following our recent demonstration that the chronic inflammatory and insulin resistant state of obesity is associated with an increase in the expression of mediators known to contribute to the pathogenesis of asthma and that weight loss after gastric bypass surgery results in the reduction of these genes, we have now hypothesized that insulin suppresses the cellular expression and plasma concentrations of these mediators. Methods. The expression of IL-4, LIGHT, LTBR, ADAM-33, and TSLP in MNC and plasma concentrations of LIGHT, TGF-β1, MMP-9, MCP-1, TSLP, and NOM in obese patients with T2DM were measured before, during, and after the infusion of a low dose (2 U/h) infusion of insulin for 4 hours. The patients were also infused with dextrose or saline for 4 hours on two separate visits and served as controls. Results. Following insulin infusion, the mRNA expression of IL-4, ADAM-33, LIGHT, and LTBR mRNA expression fell significantly (P<0.05 for all). There was also a concomitant reduction in plasma NOM, LIGHT, TGF-β1, MCP-1, and MMP-9 concentrations. Conclusions. Insulin suppresses the expression of these genes and mediators related to asthma and may, therefore, have a potential role in the treatment of asthma.